ANALYSIS OF THE APPLICATION OF ACCOUNTING INFORMATION SYSTEMS OF CASH RECEIPT ON THE RSIA KASIH IBU MANADO - Pelealu, Debora Angel; Sabijono, Harijanto (Universitas Sam Ratulangi, 2015)
The accounting information system on cash receipt is an information system that is important to improve the quality and performance of a hospital. The application of the supervision/control system in an organization will provide many benefits to the management in running the business, as well as to maintain the existence of the company in facing competitors. This study aims to analyze the application of cash receipts accounting information systems at RSIA Kasih Ibu Manado. RSIA Kasih Ibu, is one of the agencies that deal with health services for mothers and children. The method used is descriptive method. The results shows, the accounting information systems, especially cash receipts on the RSIA Kasih Ibu has been in accordance with the basic elements of accounting information systems. This is evident by the existence of good records and adequate internal control. It is recommended that the accounting information system in the financial department computerized information system is implemented in accordance with the required accounting information systems also maintain and improve the information system that has been implemented, so that the hospital can have a good quality in service, administration and finance. Keywords: accounting information systems, cash receipts